2003
DOI: 10.1016/s0008-6363(03)00293-1
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation by urocortin of rat renal arteries: effects of diabetes in males and females

Abstract: These results suggest that urocortin produces a marked vasodilation of renal arteries, which may be mediated by nitric oxide in females and by activation of potassium channels in both genders, and is reduced by diabetes in renal arteries from females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
5
13
1
Order By: Relevance
“…Indeed, urocortin-induced hyperpolarization and relaxation were markedly attenuated by the presence of charybdotoxin, a selective blocker of large conductance Ca 2+ -activated K + channels. Our findings in mesenteric arteries support previous studies carried out in rat basilar arteries (Schilling et al 1998), human saphenous veins (Sanz et al 2002) and rat renal arteries (Sanz et al 2003), in which vasorelaxations induced by urocortin were affected by blockade of Ca 2+ -activated K + channels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, urocortin-induced hyperpolarization and relaxation were markedly attenuated by the presence of charybdotoxin, a selective blocker of large conductance Ca 2+ -activated K + channels. Our findings in mesenteric arteries support previous studies carried out in rat basilar arteries (Schilling et al 1998), human saphenous veins (Sanz et al 2002) and rat renal arteries (Sanz et al 2003), in which vasorelaxations induced by urocortin were affected by blockade of Ca 2+ -activated K + channels.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in this study urocortin-induced hyperpolarization and relaxation were not affected by the presence of N G -nitro-L-arginine (nitro-Larginine), which inhibits NOS activity. Similar findings were also observed by the others, who reported that urocortin-induced relaxation was not affected by the inhibition of NOS in the coronary arteries (Terui et al 2001), human saphenous veins (Sanz et al 2002), in male rat renal arteries (Sanz et al 2003), and in the rat pulmonary arteries (Chan et al 2004). Furthermore, in this study vasodilatory response to urocortin was not affected in the presence of ODQ, which is an inhibitor of soluble guanylate cyclase (Tseng et al 2000).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed Ucn2-induced renal responses, which occurred in the face of prominent reductions in plasma atrial natriuretic peptide/brain natriuretic peptide, are similar to those seen in our earlier work with the peptide in ovine HF, [12][13][14][15] and are likely a consequence of improvements in glomerular filtration (as judged by the increase in CrCl), renal vasodilatation, 28 and attenuation of circulating antinatriuretic/antidiuretic factors (Ang II, aldosterone, and arginine vasopressin). Direct tubular actions of Ucn2 are also plausible given that not only is the CRF 2 receptor present in the proximal tubules of the kidney, 29 but also administration of the peptide is accompanied by increases in urine cAMP (Ucn2's intracellular second messenger).…”
Section: Discussionsupporting
confidence: 80%
“…However, cAMP is a second messenger utilized by many systems activated in HF, and the failure of levels to rise in the Ucn1-treated animals likely reflects the less severe disease status achieved in this group (25). Nevertheless, cAMP was raised sufficiently at the level of cell signaling to induce the significant effects observed with Ucn1 administration, or, alternatively, other pathways may be involved (22,37,42).…”
Section: Discussionmentioning
confidence: 97%